74 GPs Knowledge of and Attitudes Towards the Management of Behavioural and Psychological Symptoms of Dementia: a Descriptive Cross Sectional Study. (16th September 2019) - Jennings, Aisling A; Fatimah Dhuny, Sheefah Bibi; Foley, Tony
Abstract: Background: Evidence suggests that the current management of behavioural and psychological symptoms of dementia (BPSD) in general practice is sub-optimal. Non-pharmacological strategies are recommended first-line but uptake of these strategies is low. Despite their adverse effects and minimal effectiveness antipsychotics are frequently employed to manage BPSD. The aim of this study was to explore general practitioners (GPs) knowledge of and attitudes towards the management of BPSD with a view to informing future interventions. Methods: A questionnaire was adapted from existing study. Additional questions were included, informed by the findings of a qualitative study previously conducted by the authors. The questionnaire was piloted with 3 GPs and was posted to a census sample of all GPs in county Cork and county Kerry in the south of Ireland. Statistical analysis was performed using SPSS. Results: Of the 456 questionnaires sent 168 completed questionnaires were returned (36.8% response rate). The sample was representative of GPs nationally in terms of years of practice (p<0.0001). 62.5 % (105/168) of respondents had a nursing home commitment. The majority of GPs (60.7%) agreed that they required more training to improve their management of BPSD. 'Lack of resources in the primary care team' was cited as the main barrier to GPs recommending non-pharmacological strategies in the community. Nursing staff were identified as the group of people that most influenced the GPs prescribing of antipsychotic medications in a nursing home setting. The majority of respondents (84/168) did not monitor their prescribing of antipsychotics to people with dementia. 63.1% (106/168) of GPs were concerned that withdrawing these medications would negatively impact on the quality of life of the person with dementia. Conclusion: This study identified several factors that influenced the management of BPSD in general practice. These findings will be used to guide future interventions in this area.